Heterogeneity in money holdings across euro area countries: The role of housing - Ralph Setzer; Paul van den Noord; Guntram B. Wolff (Research On Money in the Economy (ROME), 2010)
In this paper we examine why monetary aggregates of euro area Member States have developed differently since the inception of the euro. We derive a money demand equation that incorporates housing wealth and collateral as well as substitution effects on real money holdings. Empirically, we show that cross-country differences in real balances are determined not only by income differences, a standard determinant of money demand, but also by house price developments. Higher house prices and higher user costs of housing are both associated with larger money holdings. Country-specific money holdings are also connected with structural features of the housing market.
Keywords: E41; E51; E52; 330; Money; housing; national contribution; euro area